2007
DOI: 10.1037/1093-4510.10.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Tension and opportunity in post-World War II American psychology.

Abstract: The rapid growth of post-World War II psychology in the United States led to intradisciplinary tensions and opportunities. In this article, I examine these tensions and opportunities in the context of social change from the 1950s through the present, attending specifically to the broad impact of federal funding on psychology. I argue that as psychology became a resource-rich field, it was forced to move from a narrow, parochial stance to a position as a national-level professional player that had to deal with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 95 publications
(77 reference statements)
0
32
0
1
Order By: Relevance
“…This is not the received view of the history of psychology because most historians, especially psychologist-historians, tend to focus on psychological sciences in this period. American psychological science up to the beginning of World War II was parochial in its interests and small in its infl uence (Pickren, 2007). What was looming in American psychology as the US entered WWII was the very real threat that application would overwhelm laboratory science.…”
Section: Indigenization Of Psychology: the United Statesmentioning
confidence: 99%
“…This is not the received view of the history of psychology because most historians, especially psychologist-historians, tend to focus on psychological sciences in this period. American psychological science up to the beginning of World War II was parochial in its interests and small in its infl uence (Pickren, 2007). What was looming in American psychology as the US entered WWII was the very real threat that application would overwhelm laboratory science.…”
Section: Indigenization Of Psychology: the United Statesmentioning
confidence: 99%
“…During and after World War II, American psychologists had demonstrated to the government and to the general public that their expertise could be of great use to solve various social and personal problems. The prosperous postwar America resulted in the fast growth in every area of psychology and enabled it to become a rapidly expanding industry (Pickren, , ). After the end of WWII, the United States became the major exporter of psychology and psychological education, while the Cold War era facilitated the asymmetrical international exchange of psychological knowledge from the center (the U.S.) to the non‐Western peripheries, and rarely the other way around (Danziger, ).…”
Section: The Enigma Of Scientific Psychologymentioning
confidence: 99%
“…Benjamin and Baker (2004) outlined in their book From Séance to Science: A History of the Profession of Psychology in America how professional psychology expanded quickly after the war in mental health circles. Pickren (2007) outlined the growth of professional psychology in post-World War II American psychology by focusing more specifically on the importance of large-scale federal funding. He described how in 1953 alone, the Department of Defense, the National Institute of Mental Health (NIMH), and others provided $5 million for research.…”
Section: Historical Antecedentsmentioning
confidence: 99%
“…And significant growth did occur, but within mental health. For example, Pickren (2007) reported that Division 12 (Clinical Psychology) of the APA grew from 821 members in 1948 to 2,376 members around 2005. Today, according to the APA Division Services Office, they have a total of approximately 4,000 members, making it the third largest division within the APA, interestingly now behind the Division of Clinical Neuropsychology.…”
Section: Historical Antecedentsmentioning
confidence: 99%